Women's perception on the preferences of house design for urban poor in Dhaka - Sadia Afrin, 1988-, author 603865; Tareef Hayat Khan, supervisor 604967; Fakulti Alam Bina 8041 (2016)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2016